Historical Development of College of Education, Ikere Ekiti, Nigeria, 1977-2009 - Olayanju, Oladapo Johnson (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024DO - 10.58709/niujhu.v9i2.1906, 2024)
The paper examined the historical development of college of Education, Ikere Ekiti, Nigeria. The paper traced the origin of the college. Historical research design relying on primary and secondary sources of information was adopted. The variables considered in this paper included the origin, objectives, milestones, staffing, students’ enrolments, facilities in place and impact of the college on the host communities. Findings obtained confirmed that college has succeeded in producing teachers for the basic education in Nigeria thus fulfilling the national objectives of producing teachers and the required manpower for primary and lower level of secondary education in Nigeria. The staffing, students' enrolments and the infrastructural facilities of the college have improved; and that the college is financed by the Ekiti State Government and Tertiary Education Trust Fund assistance.  The alumni of the college had contributed immensely to their alma mater. The college had impacted positively on its host communities.  Based on the discussions of this paper, it was recommended that additional infrastructural facilities be provided by the Ekiti State Government and other stakeholders in teacher education. Ekiti State Government should endeavour to increase is budgetary allocation to the college. Keywords: Historical, Development, College of Education, National Commission for Colleges of Education, Nigeria.